(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
The situation of human rights in India is a complex one, as a result of the country’s large size and tremendous diversity, its status as a developing country and a sovereign, secular, democratic republic, and its history as a former colonial territory. The Constitution of India provides for Fundamental rights, which include freedom of religion. Clauses also provide for Freedom of Speech, as well as separation of executive and judiciary and freedom of movement within the country and abroad.